A distributed learning and teaching environment across institutions based on advanced grid portal technology - Awang Hamid, Dayang Hajah Tiawa (ELSEVIER, 2012)
This study presents web-based networked information and collaborative authoring architecture as Information and Knowledge Grids. This architecture is made possible by advanced open source grid portal software in combination with distributed parallel computing system. The distributed learning and teaching grid environment are use for improving the quality of higher education as an initial stage. This Grid architecture provides reasonable and effective online assisted learning environment at the institution for any courses. The paper describes in some detail the architecture of an advanced grid portal based on parallel computing system, learning and teaching interactions and the processes of courses management over it.